Improving Students’ Vocabulary Mastery Through English Movie for Second Year Students at MAN 01 Kota Bengkulu - Dedi Efrizal (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2018)
This study was carried out to improve the students’ vocabulary mastery through English movie in MAN 01 of Bengkulu City in academi year 2017/2018. The subjects of this study were consisted of 30 students.The method used in this study was Classroom Action Research (CAR). The Clasroom Action Research design applied in this study was a collaborative classroom action research. It means that the researcher collaborated with the English teacher as an observer and collaborator. The study was carried out in three cycles. Each cycles consisted of three meetings. The data were gathered in this study through field note and test. The result of the study showed that there was improvement on students’ vocabulary mastery. Most of the students gradually gained good scores at the end of each cycles. The score of Minimum Mastery Criterion- Kriteria Ketuntasan Minimal (KKM) of English subject was 70. In pre-assessment, the result of the students score was failed, where the mean score of the students was 9,56 (very poor). In cycle 1 the result of the students score was still poor. In cycle 2 the result of the students score has some progresses, and in the cycle 3 the result of the students score has improve effectively than action in cycle before. Where the mean score of the students was 13,23 (good). In addition, there was a positive response from the English Teacher about implementing the action. In conclusion, English movie could improve students’ vocabulary mastery.